Bermain Peran, Belajar Bahasa: Inovasi Mengembangkan Kemampuan Bahasa Inggris Anak Usia Dini di Islamic Santitham Foundation School, Thailand - Aulia, Fara; Masykuroh, Khusniyati; Suchada, Suchada (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
This international KKN – PPL activity which was carried out for one month aims to develop the English language skills of young children at the Islamic Santitham Foundation School, Nakhon Si Thammarat, Thailand. The implementation stages are carried out twice a week and evaluated to see the progress of the Role Playing method activities. The results achieved from this activity were proven to be an increase in insight and better ability to communicate in English. The role playing method in the English learning process contributes to creating a fun English learning process. Support and contribution from the school as well as thorough preparation are the keys to the success of this activity. This activity program is supported by the school to continue and be developed to improve the English of students at the Islamic Santitham Foundation School.